Construction and Evaluation of a Korean Native Microbial Consortium for the Bioremediation of Diesel Fuel-Contaminated Soil in Korea - Lee, Yunho; Jeong, Sang Eun; Hur, Moonsuk; Ko, Sunghwan; Jeon, Che Ok (Frontiers in Microbiology, 2018)
A native microbial consortium for the bioremediation of soil contaminated with diesel fuel in Korea was constructed and its biodegradation ability was assessed. Microbial strains isolated from Korean terrestrial environments, with the potential to biodegrade aliphatic hydrocarbons, PAHs, and resins, were investigated and among them, eventually seven microbial strains, Acinetobacter oleivorans DR1, Corynebacterium sp. KSS-2, Pseudomonas sp. AS1, Pseudomonas sp. Neph5, Rhodococcus sp. KOS-1, Micrococcus sp. KSS-8, and Yarrowia sp. KSS-1 were selected for the construction of a microbial consortium based on their biodegradation ability, hydrophobicity, and emulsifying activity. Laboratory- and bulk-scale biodegradation tests showed that in diesel fuel-contaminated soil supplemented with nutrients (nitrogen and phosphorus), the microbial consortium clearly improved the biodegradation of total petroleum hydrocarbons, and all microbial strains constituting the microbial consortium, except for Yarrowia survived and grew well, which suggests that the microbial consortium can be used for the bioremediation of diesel fuel-contaminated soil in Korea.